Factors Associated with the Incidence of Pulmonary Tuberculosis at Cimalaka Community Health Center in 2023 - Agustiani, Nur Aeni; Andayani, Hana Fitria (PHSAJ - Public Health Sebelas April Journal, 2024)
Pulmonary TB is one of the top 10 leading causes of death globally. The Ministry of Health detected 717,941 cases of Lung TB in Indonesia in 2022, Lung TB is one of the health problems both in the world and in Indonesia with a high number of cases and deaths. The purpose of this study was to determine the relationship between the factors of Education, Occupation, Knowledge, with the incidence of Pulmonary TB at the Cimalaka Health Center in 2023. This study used a quantitative design with a cross sectional approach. The population in this study were patients who were recorded and data to the DOTS clinic at the Cimalaka Health Center from January to May 2023, namely 490 patients and the sampling technique was carried out by accidental sampling technique. The sample in this study amounted to 84 patients. Data analysis used is univariate and bivariate analysis using the chi-squere test. The results of this study showed that patients with low education amounted to 42 patients (50%), who did not have a job amounted to 58 patients (69%), and who had insufficient knowledge amounted to 39 (46.4%). It is known that there is a relationship between education and the incidence of pulmonary TB with a value (p value 0.006), there is a relationship between employment and the incidence of pulmonary TB with a value (p value = 0.001), and there is a relationship between knowledge and the incidence of pulmonary TB with a value (p value = 0.000). The statement is interpreted based on the value of the correlation coefficient and the probability of the chi squere method with alpha 0.05 means the p value <alpha then hypotheses alternative is accepted. From the results of this study, it is expected that health institutions and the community pay special attention by minimizing the causes of pulmonary TB disease.